RESPON GARUT TERHADAP JUMLAH BENIH DAN DOSIS PUPUK ORGANIK - Mentari Nurul Lathifah; Supriyono Supriyono; Mujiyo Mujiyo (Caraka Tani: Journal of Sustainable Agriculture, 2017)
Arrowroot is a plant that has not been widely cultivated in Indonesia. Arrowroot not considered to be a source of food but is often planted in the yard in the countryside as a food reserve during the dry season.Thisresearch is done to determine the number of seeds and optimum organic fertilizer dosage used for optimize growth and yield of arrowroot. Experiment  was performed in dryland of experimental field of Agriculture Faculty of SebelasMaret University in Jumantono, Karanganyar. This research was arranged using Complete Randomized Blocked Design (CRBD) factorial with 2 factors of treatment that is the number of seeds and doses of organic fertilizer.The seed quantity consists of 2 levels, which are  J1(1 seed per planting hole) and J2 (2 seeds per planting hole). The dose of organic fertilizer consist of 3 levels of P1 (2.5 ton / ha), P2 (5 ton / ha) and P3 (7.5 ton / ha). Data were analyzed using DMRT (Duncan Multiple Range Test). The results showed that the 2 seed per planting hole treatment resulted in better growth and yield of garut on the variable of leaf number, tuber length and tuber weight per plot each of them 26,11 sheet, 23,09 cm and 7,60 kg. The organic fertilizer did not give significant result to the growth and yield of the arrowroot, but organic fertilizer of 5 ton / ha dose tends to give higher yield on number of tuber, tuber weight per plot and tuber diameter.